PERIBAHASA BAHASA JEPANG DAN PADANAN MAKNA BAHASA INDONESIA DALAM NOVEL BOTCHAN KARYA NATSUME SOSEKI - Dody Guna Yasa, I Putu (Humanis; Volume 11. No2. Mei 2015, 2015)
This research entitled “Japanese proverbs and the meaning equivalent in Indonesian in the novel of Botchan written by Natsume Soseki”. The purpose of this study is to understand the meaning of Japanese proverbs and their equivalent meanings in Indonesian. This research used syntactic and contextual meaning theory according to Chaer (2009; 2007), and idiomaticall meaning theory according of Djajasudarma (2008). The methods that used were observation method, mixed methods of qualitative and quantitative method, and at last stage informal method is used. The results shows us that from 22 data founded of 26 sentences, 18 data are idiomaticall phrases and 4 data are yojijukugo (four Chinese characters combination). Japanese proverb has similar meaning in Indonesian. The idiomaticall meaning and contextual meaning of Japaneses proverbs are same without affected of time, place, and situations when we use a proverb in our conversation.
Keywords: proverb, meaning, idiomatic meaning, contextual meaning